Construction of Religious Character Values in Religious Learning at the Hamzanwadi Islamic Institute NWDI Pancor - Sugianto, Hendri; Arif, Mahmud; Usman (GHAITSA : Islamic Education Journal, 2026)
Islamic universities face increasingly complex challenges due to the development of digital technology and social changes that affect students' mindsets and behaviors. On the one hand, this progress has expanded access to science, but on the other hand, it has also had an impact on weakening religious awareness, academic ethics, and moral responsibility in campus life. This study aims to analyze the construction of religious character values in NW learning at the Hamzanwadi Nahdlatul Wathan Diniyah Islamiyah (NWDI) Pancor Islamic Institute which focuses on value construction, internalized pedagogical process, and the formation of students' religious habitus. This study uses a field qualitative approach with purposive sampling techniques. Data was obtained through interviews, observations, and documentation, then analyzed using Miles and Huberman's interactive model. The results of the study show that the value of religious character is constructed through the material of verses of the will of the devotional of the time, Shalawat Nahdlatain, the example of lecturers, and the academic culture of the campus which gives birth to the values of faith, piety, sincerity, honesty, discipline, help, religious moderation, tolerance, and love for the homeland. The internalization process takes place through teacher-centered learning, deep learning, example, habituation, lectures, contemplation, and discussion so as to form moral knowledge, value appreciation, and real actions. These academic traditions form religious habitus in the form of academic integration, social responsibility, presence towards lecturers, and moderate religiosity. This research emphasizes that NW learning is not just an institutional course, but a system of religious character formation of students who live in culture or tradition at the Hamzanwadi Islamic Institute NWDI Pancor.